An Analysis of Deleuze and Guattari’s Territorialization Anti-Oedipus Psychoanalytic Criticism in Fyodor Dostoevsky’s Notes from Underground (1864) - Hendra Sudarso; Haris Dibdyaningsih; Rizki Ramadhan (Universitas PGRI Madiun, 2022)
The unnamed character in Notes from Underground is anxious to make his life worse. The Anti-Oedipus theory of Deleuze and Guattari deals with psychological problems of people who try to make their lives worse. Territorialization is a desire to valorize certain organs and objects at the expense of others. This study applies descriptive qualitative research method since the objective is to describe and reveal how the central characters’ effort in changing his life’s condition. This study is conducted through some steps, close reading and note taking, interpreted, and concluded to identifying right quotations, phrases, dialogues and monologues. The researcher analyses and describes the results of the efforts of the unnamed central character in changing his life as theory of Deleuze and Guattari. Based on the analysis in this study, it can be concluded that the unnamed central character in Notes from Underground did some efforts to change his life in line with the Anti-Oedipus theory of Deleuze and Guattari. There are unconsciousness and consciousness desire that show how the central characters’ efforts in changing their life. Based on Deleuze and Guattari, the unnamed central character in Notes from Underground shows that his desire which supports the character to change his life condition becomes worse dominates his unconsciousness desires and his consciousness will help him to make his desire change his life condition.